2006
DOI: 10.1111/j.1365-2214.2006.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of DCD and SLI: significance of epileptiform activity during sleep

Abstract: In children with severe DCD other disabilities are frequently associated. In these children, epileptiform activity during sleep is very frequently found and in our opinion, this represents a hallmark of 'Hereditary Impairment of Brain Maturation', a term only partially resembling 'Atypical Brain Development'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 30 publications
1
31
0
4
Order By: Relevance
“…Research has demonstrated this overlap with DCD to a significant degree with ADHD, dyslexia and ASD, and there is also evidence suggesting that one-third of children with speech and language impairment are likely to have DCD as well 16 24. In addition, other medical conditions such as benign epilepsy of childhood with centrotemporal spikes (BECTS) syndrome25 and joint hypermobility syndrome (JHS26) have also been associated with DCD. However, despite this compelling evidence showing the heterogeneous nature of DCD, it is not routinely considered by clinicians and remains the ‘Cinderella’ of developmental disorders 27.…”
Section: Coexisting Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated this overlap with DCD to a significant degree with ADHD, dyslexia and ASD, and there is also evidence suggesting that one-third of children with speech and language impairment are likely to have DCD as well 16 24. In addition, other medical conditions such as benign epilepsy of childhood with centrotemporal spikes (BECTS) syndrome25 and joint hypermobility syndrome (JHS26) have also been associated with DCD. However, despite this compelling evidence showing the heterogeneous nature of DCD, it is not routinely considered by clinicians and remains the ‘Cinderella’ of developmental disorders 27.…”
Section: Coexisting Disordersmentioning
confidence: 99%
“…Observation of muscle tone in sitting and standing may give an impression of the ability of the child to maintain their posture against gravity (eg, slumped). Motor sequencing using finger to thumb in sequence may reveal some associated movements, also known as overflow or mirror movements; however, these are not diagnostic because they are also commonly seen in young typically developing children, but may along with other features be an alerting sign 25. A fine tremor, difficulties with heel–toe walking and past-pointing may indicate the presence of cerebellar pathology.…”
Section: Assessment Of Dcdmentioning
confidence: 99%
“…The childhood epilepsy cases reported were BECCTS syndrome (Benign Epilepsy of Childhood with Centrotemporal Spikes) and has been associated with motor difficulties (Scabar et al,2006) but were excluded because of a known neurological condition.…”
Section: Total Reported 14mentioning
confidence: 99%
“…In the literature, the neuropsychological outcome of CSWS and its correlations with etiology, duration, and therapy are still unclear, due to the relative few longitudinal studies on the disorder and the clinical heterogeneity [26][27][28][29][30][31][32]. The knowledge of the developmental clinical picture and its correlations with etiologic, neuropsychiatric, and therapeutic factors is important for early treatment and prognosis.…”
Section: Discussionmentioning
confidence: 99%